Dermatological manifestations in cardiofaciocutaneous syndrome: a prospective multicentric study of 45 mutation‐positive patients3. (30th September 2018) - Bessis, D.; Morice‐Picard, F.; Bourrat, E.; Abadie, C.; Aouinti, S.; Baumann, C.; Best, M.; Bursztejn, A.‐C.; Capri, Y.; Chiaverini, C.; Coubes, C.; Giuliano, F.; et al.
Summary: Background: Data on dermatological manifestations of cardiofaciocutaneous syndrome (CFCS) remain heterogeneous and almost without expert dermatological classification. Objectives: To describe the dermatological manifestations of CFCS; to compare them with the literature findings; to assess those discriminating CFCS from other RASopathies, including Noonan syndrome (NS) and Costello syndrome (CS); and to test for dermatological phenotype–genotype correlations. Methods: We performed a 4‐year, large, prospective, multicentric, collaborative dermatological and genetic study. Results: Forty‐five patients were enrolled. Hair abnormalities were ubiquitous, including scarcity or absence of eyebrows and wavy or curly hair in 73% and 69% of patients, respectively. Keratosis pilaris (KP), ulerythema ophryogenes (UO), palmoplantar hyperkeratosis (PPHK) and multiple melanocytic naevi (MMN; over 50 naevi) were noted in 82%, 44%, 27% and 29% of patients, respectively. Scarcity or absence of eyebrows, association of UO and PPHK, diffuse KP and MMN best differentiated CFCS from NS and CS. Oral acitretin may be highly beneficial for therapeutic management of PPHK, whereas treatment of UO by topical sirolimus 1% failed. No significant dermatological phenotype–genotype correlation was determined. Conclusions: A thorough knowledge of CFCS skin manifestations would help in making a positive diagnosis and differentiating CFCS from CS and NS. Abstract : What's already known about this topic? Data on dermatological manifestations of cardiofaciocutaneous syndrome (CFCS) remain heterogeneous and almost without expert dermatological input. Dermatological findings remain essential to diagnose CFCS and to differentiate it from other RASopathies that it resembles phenotypically, specifically Noonan syndrome (NS) and Costello syndrome (CS). What does this study add? Scarcity or absence of eyebrows, association of ulerythema ophryogenes and palmoplantar keratoderma, diffuse keratosis pilaris and multiple melanocytic naevi appeared pertinent manifestations in assisting the positive diagnosis of CFCS and differentiating it from CS and NS. Oral acitretin could be highly beneficial for therapeutic management of PPHK. No significant dermatological phenotype–genotype correlation in the presence or absence of BRAF mutation could be determined. Linked Comment: Moss. Br J Dermatol 2019;180 :21 . Plain language summary available online Respond to this article